Issues, theory, and research in industrial/organizational psychology - Kelley, Kathryn (Advances in psychology (Amsterdam, Netherlands), 1992)
Industrial/Organizational psychologists are a rather diverse group of people with a common interest in applying psychology to work settings. This is the conclusion reached by George Alliger in the opening chapter of this volume, setting the tone for the rest of the book, which attempts to expand our view of what can be considered as I/O psychology. The authors of the individual chapters are from a variety of backgrounds, not all of them directly associated with I/O psychology, and they discuss topics such as managerial success and training, as well as topics much more on the edge of I/O such as team-building and organizational theory. Thus, this volume makes an important statement about the potential diversity of our field. At the same time, it will help move us towards that diversity by providing insights and information in areas that should be, and are becoming part of the realm of I/O psychology. These insights into non-traditional topics, as well as particularly interesting approaches to more traditional areas, make this volume worthwhile and useful to almost anyone concerned with I/O psychology.